Screen printed carbon electrode sensor with thiol graphene quantum dots and gold nanoparticles for voltammetric determination of solatol - Roushani, Mahmoud (Heliyon, 2019)
This work, a highly selective and sensitive sensor is described for voltammetric determination of the sotalol (SOT). The dual actions of sotalol lead to reductions in the automaticity of myocardial cells and in conduction through the atrioventricular node. Drug analysis has an extensive impact on public health. The molecularly imprinted sensor was constructed by modifying a screen printed carbon electrode (SPCE) with thiol graphene quantum dots (GQD-SH) and gold nanoparticles (AuNPs). Under optimal conditions the nanotools has a dynamic range that covers the 0.1–250 μM SOT concentration range, and the detection limit is 0.035 μM. This is lower than any of the previously reported methods. The MIP-sensor also exhibited excellent selectivity, good stability and adequate reproducibility for the detection of the SOT over its structural analogs. The prepared sensor was successfully applied to the measurement of SOT in various real samples including tablet and human blood serum.